Marketing Communication Strategy By Mr.kickshoescare Store in An Effort To Increase Sales - Faruq Izzudin Al Qosam; Lalu Ahmad Taubih (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2022)
This study describes the marketing communication strategy used by the Mr. Kickshoescare store in finding and increasing the sales of the products they have. In this study, the author uses Kotler and Keller's STP theory (Segmenting, Targeting & Positioning) which is a theory used to map the community, determine the target market and determine the company's ultimate goal based on the results of segmentation and target market. This study also uses descriptive qualitative research methods, with data collection techniques by observation, interviews and documentation. While the determination of informants in this study was determined by purposive sampling technique and the data analysis technique used data analysis techniques from Miles and Huberman, namely data reduction, data presentation and conclusion drawing. Based on the research results, Mr. Kickshoescare store uses the STP (segmentation, targeting, & positioning) strategy as the first step before doing marketing. The marketing strategy used is to use Instagram as a means of marketing products from the Mr. Kickshoescare store based on the results of the previous STP (segmentation, targeting, & positioning) strategy. For segmentation, there are four aspects to be considered, namely geographic segmentation, demographic segmentation, psychographic segmentation, and basic behavior segmentation. In addition, Mr. Kickshoescare has a target market in the form of full market coverage where the store serves all the needs of all circles and positioning those who want to be the first store providing shoe washing services that have the best service in Subang Regency.